A recombinant subunit vaccine for the control of ovine psoroptic mange (sheep scab). (December 2016) - Burgess, Stewart; Nunn, Francesca; Nath, Mintu; Frew, David; Wells, Beth; Marr, Edward; Huntley, John; McNeilly, Tom; Nisbet, Alasdair
Abstract Sheep scab, caused by infestation with the mitePsoroptes ovis, is highly contagious, causing intense pruritus and represents a major welfare and economic concern. Disease control strategies rely upon chemotherapy, however, sustainability is questionable due to issues of chemical residues, eco-toxicity and acaricide resistance. Control by vaccination is supported by demonstration of protective immunity in sheep previously infested withP. ovis . We identified vaccine candidates forP. ovis based on: (1) antigens selected by their interaction with host signalling pathways and the host immune-response; and (2) those shown to be either immunogenic or involved in mite feeding. This resulted in the development and validation, in repeated immunisation and challenge trials, of a seven recombinant protein sub-unit cocktail vaccine. Sheep were inoculated on three occasions, 2 weeks apart, along with QuilA adjuvant. Vaccination resulted in highly significant reductions in both lesion size (up to 63%) and mite numbers (up to 56%) following challenge. Mean lesion size in vaccinates was significantly smaller than controls from 1 week post infestation (wpi) until the end of the experiment at 6 wpi. All antigens elicited serum IgG responses following immunisation and prior to infestation, whereas controls did not produce antigen-specific IgG during the pre-infestation period. Vaccinated animals showed an amnestic response, with levels of antigen-specific IgG against muGST, Pso o 1 and Pso o 2 increasing following infestation. This vaccine represents the greatest reduction in lesion size to date with a sheep scab vaccine, providing encouragement for future production of a commercially-viable means of immunoprophylaxis.